Salivary Fluoride Bioavailability after Brushing with Brazilian Red Propolis Dentifrice: A Clinical Study. (31st January 2022) - Girão Júnior, Francisco Josimar; Valadas, Lidia Audrey Rocha; Bottenberg, Peter; Lotif, Mara Assef Leitão; Rodrigues Neto, Edilson Martins; Fonseca, Said Gonçalves da Cruz; Bandeira, Mary Anne Medeiros; Squassi, Aldo; Dantas, Thereza Cristina Farias Botelho; Sena, Nara Juliana Custódio de; Fonteles, Marta Maria de França
Abstract : Introduction . Fluoride plays an important role in the control of dental caries, and currently new dentifrices are being associated with natural products. Objective . This study aimed to evaluate the availability of fluoride in saliva samples after using a dentifrice incorporated with Brazilian red propolis (BRP, INPI Patent no. BR1020170110974) and to compare it to a conventional fluoridated dentifrice in healthy participants. Methods . This study was conducted implementing a double-blind, randomized, controlled, and crossover design. Saliva samples of participants were collected at the following time points: 0 at baseline and 5, 15, 30, 45, and 60 minutes after brushing with each dentifrice. Salivary fluoride concentrations showed no statistically significant difference when comparing the two treatments (p > 0.05 ). All available fluoride concentrations in saliva decreased after one hour, with no significant difference between BRP and conventional fluoridated dentifrice treatment samples (p > 0.05 ). Results . The results showed that there was no difference between the analyzed fluoride concentrations 1 hour after brushing with the different dentifrices. Conclusions . The results of this study suggest that the propolis incorporated in the dentifrice did not interfere with the kinetics and bioavailability of the fluoride ion in saliva samples, enabling its integration with the pharmaceutical formula and thereby promoting its anti-inflammatory and antimicrobial benefits without compromising the anticaries activity of the formulation.